Prescription Opioid Education Provided by Dentists to Patients following Third Molar Extractions - Pandoria, Mahima (East Carolina University, 2020)
Opioids are a group of chemically similar drugs that include heroin and prescription pain relievers such as hydrocodone, oxycodone, and morphine (Ahrnsbrak, 2016). In the United States, dentists prescribe 6.4% of all opioid prescriptions (Koppen, Suda, Rowan, McGregor, & Evans, 2018). The most common dental procedure that is often prescribed postprocedural opioids such as hydrocodone and oxycodone is third molar extractions (Gupta et al., 2018). Studies have shown that most patients reported having unused opioid medication leftovers following a procedure. Adolescents, a population that commonly undergoes third molar extractions, report unsupervised access to opioid medications in the home (Ross-Durow, McCabe, & Boyd, 2013). Safe handling of opioid medications in the home is a major concern because of their potential for nonmedical use which could lead to substance use disorder (SUD), other substance use, and overdose deaths. Following third molar extractions, dentists have the opportunity to educate patients and their caregivers on ways to minimize risks of having opioid medications in the home. The objective of this study is to assess the prevalence of education on opioid handling provided to adolescent and young adult patients by dentists and the relationship between the provision of education and secure storage of opioid medications in the home. A cross-sectional survey was used to collect information about experiences with post-procedural medications for third molar extractions. The population that we recruited for the survey was East Carolina University students ranging in age from 18-23. This survey was distributed via the Honors ListServ, fliers were placed around ECU’s campus, and fliers were posted in local dental offices. IRB approval was obtained for this study. Results pertaining to the prevalence of education on opioid handling provided to adolescent and young adult patients by dentists and the relationship between the provision of education and secure storage of opioid medications in the home led to the conclusion that there is room for improvement on dental practices that can impact patient opioid handling behavior. The findings from this study will help to gain a better understanding of dental opioid prescribing practices, which can help to identify opportunities for greater education and intervention to prevent patient nonmedical use of prescribed opioids.
Keywords: Opioid; dental offices